Kontruksi Makna Selebgram Perempuan Yang Mengalami Body Shaming - Revian Patria Allraysa; Siti Nursanti; Yanti Tayo (Peneliti.net, 2022)
It is undeniable that every social environment has its own ideal beauty standards. In a social interaction, body shape is something that is often judged by a woman. This is what causes women, especially those who do not meet the ideal beauty standards in their environment, to experience body shaming, body shaming is an activity to humiliate, ridicule, and comment on a person's physical form, body shaming can trigger body shaming or feelings of shame that arise when other people's judgments and self-assessment are not in accordance with the ideal self that is set. This body shaming phenomenon makes the writer interested in conducting research on female celebrities who experience body shaming to find out the meaning of body shaming and the meaning of self from female celebrities. The author uses a qualitative method with a phenomenological approach. The theories used include Alfred Schutz's phenomenology and the theory of the construction of social reality. The results show that each informant has a different meaning, which is influenced by the social environment, family and how the informant interprets himself. The meaning of body shaming as motivation, as pressure, and as a demand. While the meaning of self, as a valuable woman, as a woman who is not worth it.